Africa becomes electric. - Applewhite, A.
Sten Bergman is helping African villagers, far from the grid, get cheap and efficient power. As the Swedish Development Agency's representative to the World Bank's Africa Rural and Renewable Energy Initiative, Bergman is charged with helping set "a new template for rural electrification in Africa." That means scouting out low-cost energy technologies to match local needs, as well as explaining those technologies to government ministries, local leaders, utilities, "and the man in the street." The Initiative's philosophy is a radical departure from traditional development approaches. Rather than pursuing the centralized power systems favored by big utilities and international lending agencies, the initiative encourages the private sector to develop small independent grids in remote regions. The whole concept behind this African initiative is to channel electrical resources into activities that have an economic return.
Keywords: Africa; African villagers; Swedish Development Agency; World Bank's Africa Rural and Renewable Energy Initiative; Electrical resources; Low-cost energy technologies; Private sector; Remote regions; Rural electrification; Small independent grids development